2011
DOI: 10.1111/j.1600-048x.2011.05461.x
|View full text |Cite
|
Sign up to set email alerts
|

Young and female-biased irruptions in pygmy owls Glaucidium passerinum in southern Finland

Abstract: Irruptive migrants often show biased sex and age ratio, and typically young females are the most abundant class participating in irruptions. Several hypotheses have been proposed to explain differential migration in birds. We examined these hypotheses in a sexually size‐dimorphic species (females being larger than males), the pygmy owl Glaucidium passerinum, whose migration behaviour has also been poorly documented. Migration data were collected at the Hanko Bird Observatory, SW Finland during 1979–2010. Pygmy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Our study indicates that the age of migrating birds, or if interpreted slightly differently, the breeding area residence time is far from constant and becomes shorter with progressing hatching date. Similar results of late hatched individuals starting their migratory restlessness at a young age has been found in three species in aviary studies (Pulido et al 2001, Styrsky et al 2004, Helm et al 2005), but two individual‐based studies done in the wild found a constant migration age regardless of hatching date (Donaghy et al 2011, Lehikoinen et al 2011). Population level studies have also shown that several long‐ and short‐distance migrants migrate at younger age in years with late breeding (Bojarinova et al 2002, Sokolov 2006).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our study indicates that the age of migrating birds, or if interpreted slightly differently, the breeding area residence time is far from constant and becomes shorter with progressing hatching date. Similar results of late hatched individuals starting their migratory restlessness at a young age has been found in three species in aviary studies (Pulido et al 2001, Styrsky et al 2004, Helm et al 2005), but two individual‐based studies done in the wild found a constant migration age regardless of hatching date (Donaghy et al 2011, Lehikoinen et al 2011). Population level studies have also shown that several long‐ and short‐distance migrants migrate at younger age in years with late breeding (Bojarinova et al 2002, Sokolov 2006).…”
Section: Discussionsupporting
confidence: 78%
“…It is also noteworthy that, like in the tit species, our early‐hatched hawks had tendency to migrate early. Nevertheless, it seems that the connection between hatching and migration dates is much weaker than in single‐brooded irruptive pygmy owls (Lehikoinen et al 2011). Pygmy owls tend to migrate only during poor food conditions and thus early migrating can be beneficial, since early birds may get the best wintering territories in this hoarding species (Lehikoinen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the mid-1990s, the data reflect the real changes in the population and indicate how the Pygmy Owl population has increased during favourable circumstances to a very high level and after that crashed owing to the strong autumn invasion in 2003 and 2009 detected at coastal bird observatories (e.g. Lehikoinen et al 2011). The present data show that Pygmy Owls, which participated in the mass invasion, disappeared from the Finnish population.…”
Section: Year / Letomentioning
confidence: 66%